Effects of robot-assisted task-oriented upper limb motor training on neuroplasticity in stroke patients with different degrees of motor dysfunction: A neuroimaging motor evaluation index - Xie, Hui; Li, Xin; Huang, Wenhao; Yin, Jiahui; Luo, Cailing; Li, Zengyong; Dou, Zulin (Frontiers in Neuroscience, 2022)
Introduction. Although robot-assisted task-oriented upper limb (UL) motor training had been shown to be effective for UL functional rehabilitation after stroke, it did not improve UL motor function more than conventional therapy. Due to the lack of evaluation of neurological indicators, it was difficult to confirm the robot treatment parameters and clinical efficacy in a timely manner. This study aimed to explore the changes of neuroplasticity induced by robot-assisted task-oriented UL motor training in different degrees of dysfunction patients and extract neurological evaluation indicators to provide the robot with additional parameters information. Materials and Methods. A total of thirty-three adult patients with hemiplegic motor impairment after stroke were recruited as participants in this study and according manual muscle test divided patients into muscle strength 0-1 level (severe group, n=10), 2-3 level (moderate group, n=14), and 4 or above level (mild group, n=9). Tissue concentration of oxyhemoglobin and deoxyhemoglobin oscillations in the bilateral prefrontal cortex, dorsolateral prefrontal cortex (DLPFC), superior frontal cortex (SFC), premotor cortex, primary motor cortex (M1), primary somatosensory cortex (S1) and occipital cortex were measured by functional near-infrared spectroscopy (fNIRS) in resting and motor training state. The phase information of a 0.01-0.08 Hz signal was identified by the wavelet transform method. The wavelet amplitude, lateralization index and wavelet phase coherence (WPCO) were calculated to describe the frequency-specific cortical changes. Results. Compared with resting state, significantly increased cortical activation were observed in ipsilesional SFC in mild, and bilateral SFC in moderate group during UL motor training. Patients in mild group demonstrated significantly decreased lateralization of activation in motor training than resting state. Moreover, WPCO value of motor training between contralesional DLPFC and ipsilesional SFC, bilateral SFC, contralesional S1 and ipsilesional M1 were showed significantly decrease compared with resting state in mild group. Conclusions. Robot-assisted task-oriented UL motor training could modify neuroplasticity of SFC and contribute to control movements and continuous learning motor regularity for patients. fNIRS could provide a variety of real-time sensitive neural evaluation indicators for the robot, which was beneficial to formulating more reasonable and effective personalized prescriptions during motor training.